Consumer acceptance of enhanced seat belt reminders, a gearshift interlock, or different speed-limiting interlocks to encourage seat belt use following a brief hands-on experience. (December 2019) - Kidd, David G.; Singer, Jeremiah
Highlights: 28 volunteers drove 6 vehicles with a belt reminder or interlock on a closed course. Opinions of the technologies were collected using a survey after each drive. Interlocks were perceived as more effective for increasing belt use than reminders. Interlocks were perceived as no more or less acceptable than reminders. Volunteers raised safety concerns unique to interlocks that may impede acceptance. Abstract: Seat belt interlock systems that restrict the use of the vehicle or a vehicle feature when an occupant is unbelted are effective for increasing seat belt use but might be unacceptable to consumers. This study collected driver opinions about whether 3 seat belt reminder systems and 3 interlock systems, two that restricted speed and one that prevented shifting into gear, would increase belt use and were acceptable. Twenty-eight volunteers, 22 who routinely did use a belt and 6 who routinely did, drove 6 vehicles with these technologies on a closed course while unbelted or completing tasks that led to unbelted driving. Participants indicated their level of agreement from 1 (strongly disagree) to 5 (strongly agree) with 5 statements after driving each vehicle. Participants reported stronger levels of agreement that each interlock system would make them buckle up more frequently than 2 of the 3 reminder systems. Agreement about finding the various technologies acceptable, requiring them in a vehicle, avoiding purchasing a vehicle with them, or circumventing them was not significantly different among technologies. When asked to circumvent each interlock system, participants most commonly sat on a buckled belt, routed the belt behind their back, or buckled and unbuckled in various manners. Most participants raised safety concerns in a post-study interview about the interlock systems, particularly those that restricted speed. Hence, although interlocks were perceived as more effective for increasing belt use and no more or less acceptable than reminders following a brief hands-on experience, interlocks created safety concerns that may impede acceptance.